Digital Competence of Medical Personnel: A Systematic Literature Review and Meta-Analysis - Ferdy.T. Rumambi; Lawren Julio Rumokoy; Christoffel M. O. Mintardjo; Fitty Valdi Arie (Journal of Creative Power and Ambition (JCPA), 2026)
Digital competence among healthcare professionals has become increasingly essential for ensuring high-quality patient care and adapting to the rapid advancement of healthcare technologies. Therefore, this systematic review and meta-analysis aimed to synthesize existing evidence regarding digital competence levels among healthcare professionals, identify the key factors associated with digital competence, and evaluate the effectiveness of digital competence training interventions. A comprehensive search of PubMed, Scopus, Web of Science, and ERIC databases was conducted for studies published between January 2015 and December 2023. Observational and quasi-experimental studies involving physicians, nurses, and other healthcare professionals were included, with screening, data extraction, and risk-of-bias assessment independently performed by two reviewers using the Newcastle-Ottawa Scale. Meta-analysis was conducted using a random-effects model. A total of 47 studies involving 12,356 participants from 28 countries met the inclusion criteria. The pooled mean digital competence score was 68.2% (95% CI: 64.8–71.6%), with significant differences observed across professional groups and healthcare settings. Physicians demonstrated higher competence levels (71.4%) than nurses (66.3%) (p = 0.003), while healthcare personnel working in tertiary hospitals showed greater competence (72.1%) compared with those in primary care settings (61.5%) (p < 0.001). Important predictors of digital competence included age, years of professional experience, and formal information technology training. Furthermore, digital competence training interventions significantly improved competence levels by 18.5% (95% CI: 14.2–22.8%; I² = 58%). Overall, the quality of evidence was moderate for most outcomes, indicating that targeted training programs can play a substantial role in enhancing digital competence among healthcare professionals.